João Köpke e a escola republicana: criador de leituras, escritor da modernidade - Silva, Claudia Panizzolo Batista da (2006)
This work in a historiographic study of the intellectual and professional trajectory of João Kopke [ 1852 1926 ] educator involved in the republican cause, marked by an innovative and creative restlessness, by a coherence of principles and by the pioneerism in the divulgation of modern ideas and pedagogical practices. A multifaceted intellectual and one of the most significant educators of his generation to put in circulation, in the press and in the schools where he worked, a modern and republican pedagogy defined by an updated curriculum, practical, concrete and scientific teaching; an intuitive methodology through lessons of things; serial, graduated and simultaneous classes; extra-class activities ; popular and pedagogical lectures and by the analytical teaching of reading from a long time deserved a more detailed study that would consider him inside the frame pictures of the History of Education . To take him from forgetfulness, to study the educator, to focus the singularities of Joao Köpke as an intelectual of Education and at the same time, to examine his preoccupation and challenges , the polemics assumed by him and by his co-workers is what this research aims for. The investigation about his intellectual trajectory, the study of the schools where he worked, the analysis of his first reader books , of his lectures and of his reading books, destined to elementary and high school teaching, as well as the exam of the pieces of news published about his multiple activities in São Paulo and Rio de Janeiro show that João Köpke was moved by a political and intellectual project well characteristical , an assurance of a unity of sense, present in his attitudes and in the writings that he developed for more than fifty years